Emergency Physician–Administered Sedation for Thoracostomy in Children With Pleuropneumonia. Issue 12 (11th December 2021) - Tel-Dan, Shira Fajnerman; Shavit, Danielle; Nates, Ron; Samuel, Nir; Shavit, Itai
Abstract : Background: Thoracostomy drainage is sometimes required in children with pleuropneumonia who have large parapneumonic effusion. This procedure is usually performed under sedation. The aim was to report sedation adverse events (SAEs) in pneumonia patients sedated for thoracostomy by pediatric emergency physicians. Methods: A retrospective cohort study was conducted. The medical records of all emergency department patients who underwent thoracostomy between January 1, 2012, and December 31, 2018, were extracted. Study outcomes were SAEs that required intervention. Results: Pigtail catheters were placed by chest surgeons in 28 children with a median age of 2 years (interquartile range [IQR], 1–5 years). All the thoracostomies were successfully performed under sedation performed by 11 pediatric emergency physicians. The median amount of fluid drained after catheter insertion was 200 mL (IQR, 100–500 mL). The median pleural fluid PH was 7.0 (IQR, 6.9–7.3), and the median white blood cell count was 34, 600 per mm 3 (IQR, 11, 800–109, 000 per mm 3 ). Thirteen patients (46.4%) were sedated with a total median dose of 3 mg/kg of ketamine (IQR, 2–4 mg/kg) and 0.2 mg/kg of midazolam (IQR, 0.2–0.3 mg/kg); 11 patients (39.3%) were treated with 1 mg/kg of ketamine (IQR, 0.5–2 mg/kg) and 3 mg/kg of propofol (IQR, 2–4 mg/kg). Four patients (14.3%) were treated exclusively with 4 mg/kg of ketamine (IQR, 3–5 mg/kg). Nine oxygen desaturations required intervention; 1 was associated with laryngospasm and 1 with apnea. All the SAEs were successfully managed. No cases of hypotension, bradycardia, airway obstruction, or pulmonary aspiration were recorded. Conclusions: The first series of pneumonia patients sedated for thoracostomy by pediatric emergency physicians is reported. Sedation was safely performed in this cohort.